2016
DOI: 10.1016/j.molp.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

PIF1 Regulates Plastid Development by Repressing Photosynthetic Genes in the Endodermis

Abstract: Mutations in Phytochrome Interacting Factors (PIFs) induce a conversion of the endodermal amyloplasts necessary for gravity sensing to plastids with developed thylakoids accompanied by abnormal activation of photosynthetic genes in the dark. In this study, we investigated how PIFs regulate endodermal plastid development by performing comparative transcriptome analysis. We show that both endodermal expression of PIF1 and global expression of the PIF quartet induce transcriptional changes in genes enriched for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 64 publications
2
25
0
1
Order By: Relevance
“…Similarly to hypocotyl elongation, both epidermal and vascular PIF4 failed to rescue the hypocotyl negative gravitropism of pifq mutants (Fig. 5c), consistent with previous studies showing that endodermal PIFs mediate negative hypocotyl gravitropism 37,57 .…”
Section: Role Of Epidermal and Vascular Pif4 In Skotomorphogenesissupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly to hypocotyl elongation, both epidermal and vascular PIF4 failed to rescue the hypocotyl negative gravitropism of pifq mutants (Fig. 5c), consistent with previous studies showing that endodermal PIFs mediate negative hypocotyl gravitropism 37,57 .…”
Section: Role Of Epidermal and Vascular Pif4 In Skotomorphogenesissupporting
confidence: 91%
“…Although the functional roles of PIF4 in the regulation of growth and development of aerial tissues have been extensively studied, the tissue-specific roles of PIF4 are still poorly understood. It was previously shown that PIF4 overexpression in vasculature promotes flowering, and endodermal PIF1, a PIF4 homolog, regulates hypocotyl negative gravitropism [37][38][39] . Surprisingly, it was reported that epidermal, but not endodermal, phyB activity is required for light regulation of hypocotyl negative gravitropism 40 .…”
mentioning
confidence: 99%
“…The leaves of transformants had numerous cells, but the chloroplasts in the leaves were of a smaller size (Figure 7B, indicated by white arrowheads). Furthermore, the expression of the photosynthetic gene light harvesting chlorophyll a/b binding protein (lhcb ) in the leaves was also investigated (Figure 7C; Kim et al, 2016). RNA isolated from CK was used as a negative control.…”
Section: Resultsmentioning
confidence: 99%
“…2; Shi et al, 2013;Lee et al, 2015). PIF1 also regulates chlorophyll biosynthesis and plastid development by modulating the expression of a number of genes Moon et al, 2008;Kim et al, 2016c). PIF2 (more commonly known as PIL1) also interacts with COP1 and phyB in vivo ( Fig.…”
Section: Distinct and Shared Biological Functions Of Pifs In Arabidopsismentioning
confidence: 99%